PENGARUH EKUITAS MEREK DAN INOVASI TERHADAP KEPUTUSAN PEMBELIAN DIMEDIASI HARGA DI APLIKASI TOKOPEDIA - Cahyo Nugroho, Azhar; Budiarti, Anindhtya (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This study is entitled brand equity and innovation have an influence on price-mediated purchasing decisions in the Tokopedia application for students of the Indonesian College of Economics (STIESIA) Surabaya class of 2019 morning class. This study aims to determine whether brand equity and innovation have an influence on price-mediated purchasing decisions in the Tokopedia application for students of the Indonesian College of Economics (STIESIA) Surabaya class of 2019 morning class. The type of research used in this study is quantitative. The sampling technique used in this study was the nonprobality sampling method which is a technique for selecting sample members by providing restrictions to respondents who meet the criteria. Data collection used through the distribution of questionnaires with a sample size of 80 respondents. The data analysis technique used in this study is the PLS (Partial Least Square) technique using supporting instruments, namely SmartPLS 3.0 software. The results of this study indicate that brand equity and innovation have a significant effect on purchasing decisions. Brand equity and innovation on purchasing decisions with price as an Intervening Variable have a significant effect